Rediscovering Ancient India: Sanskrit As a Pathway To India’s Timeless Wisdom - Dr. Anviti Rawat, Priya Swami (Journal of Informatics Education and Research, 2025)
India possesses one of the most extensive linguistic diversities globally. Despite not being widely used today, ancient Sanskrit provides a live link to India's enormous traditional knowledge base. This paper examines the difficulties caused by language loss, the ways in which Sanskrit ties contemporary India to its ancient customs, and the limitations of translation in capturing the richness of the source ideas. It also explores at how the National Education Policy (NEP) 2020 and other institutional and state-level efforts might help protect endangered languages like Sanskrit. As part of a larger initiative to preserve intellectual diversity and cultural continuity, this paperalso explores the role that politics play in protecting not just Sanskrit but also India's endangered languages.It is not just a language; it is the key that unlocks the treasure chest of India’s ancient wisdom. For thousands of years the saints, scholars and thinkers used this language to put and record their ideas in the field of philosophy, mathematics, medicine, astronomy, literature and governance. The loss of Sanskrit or its weakening in education risks breaking the bridge to this vast heritage. In absence of Sanskrit, a significant portion of the knowledge would have been lost, misinterpreted or fragmented into incomplete portions.By combining qualitative research by academic studies,institutional reports and policy documents, this study offers a comprehensive perspective and understanding on how Sanskrit’s preservation is essential for sustaining India’s timeless dialogue between past, present, and future.